Study of Electrical and Dielectric Properties of Dielectric Barrier Discharges (DBD) Generated by Silicon Diode for Alternating Current (SIDAC) in Water - Truong Thi Hoa
Chapter 1: Introduction; Chapter 2: Properties of Dielectric Barrier Discharges (DBD) generation using Silicon Diodes for Alternating Current (SIDAC) in water; Chapter 3: Novel design of high voltage pulse source for efficient DBD plasma generation by using SIDAC; ...